Common Types Of Crime And Deviance Among University Students In Kenya. The Case Of Njoro Campus Of Egerton University - Murenga, Hadija Matuli (Advances in Social Sciences Research Journal, 2019)
The study aimed at exploring the common types of crime and deviance among university students in Kenya, the case of Njoro Campus, Egerton University. A sample of 67 undergraduate students was drawn from eight (8) faculties at various levels of academics. The study found that theft and drug and alcohol abuse were the most common crimes while sexual immorality was the most common type of deviance action committed by students. The study concluded that opportunity crimes and deviance were the most rampant in Njoro Campus of Egerton University. Such crimes and deviance are facilitated by the presence of suitable targets, presence of motivated offenders and absence of capable guardians to guard against actions of crime and deviance. The study recommended that the problem of crime and deviance is real in the university and stern measures need to be taken by the university management to get the situation under control and reduce levels of crime and deviance for a more tolerable environment for all students. The study also recommended that thorough investigations should be done on cases of crime and deviance and those found guilty punished accordingly. The security department should work closely with Njoro Police Station especially on serious offences committed both inside and outside the university space such as external drug peddling. This is to serve a stern warning to any other students who may wish to commit such a crime.